THE BENEFITS OF SEA TOLL IN SUPPORTING INTER-ISLAND CONNECTIVITY UNDER JOKO WIDODO'S ADMINISTRATION - Dwipayana, Eska (Institut Pendidikan Indonesia, 2025)
Developing inter-island connectivity in Indonesia is crucial to support economic growth and equitable development, especially for isolated, frontier, and outermost (3T) areas. The Sea Toll program is one of the main policies implemented by the Joko Widodo’s administration to overcome logistical challenges and price disparities between regions. This study aims to analyze the benefits of the Sea Toll in improving inter-island connectivity and its impact on Indonesia's economic, social, and logistics distribution sectors. Using a descriptive qualitative analysis method based on literature studies and secondary data, this study evaluates the effectiveness of the Sea Toll in reducing logistics costs, increasing the affordability of goods in remote areas, and accelerating the distribution of goods and services. The results show that this program contributes to improving the efficiency of sea transportation and equitable economic development in various regions. However, it still faces challenges such as supporting infrastructure and policy sustainability. Therefore, optimizing the Sea Toll program through synergy between the government, private sector, and society is key to realizing a more effective and sustainable maritime transportation system in Indonesia.